Os argumentos da razão e da moral em Milagres de C. S. Lewis - Cordeiro, Thais Cunha Cavalcanti Ferreira (2021)
The present research aims to understand the possible contribution of C. S. Lewis’ book, Miracles, regarding the arguments of morality and reason contributing to the understanding and justification of the supernatural and miracles possibility existence, which uses a logical-analytical approach. Observing and analyzing Lewis’ arguments, we analyze the dimension of his arguments’ plausibility, as well as the author's success to achieve the objectives he proposes in the work Miracles, which is to indicate reason and human moral as evidence of the existence of the supernatural, but not as an absolute proof about this. For this, we are going to observe the author's understanding about the concepts of naturalism and supernaturalism, besides the concepts of terms and the basis of the arguments of “reason” and “morals” committed and elaborated by Lewis. Thus, the analysis of Lewis' arguments is delimited on those about the question of the miracles of creation, not analyzing, therefore, those that deal with the miracles of intervention.